Resistance of common bean lines to the potato leafhopper (Homoptera: Cicadellidae) - Schaafsma, AW; Cardona Mejía, César; Kornegay, Julia L.; Wylde, AM; Michaels, TE (1998)
In 1993, seed from the EMP series reportedly resistant to leafhoppers (Empoasca Kraemeri Ross & Moore), was obtained from Centro Internacional de Agricultura Tropical (CIAT), South America and planted at Ridgetown, ON. Under severe potato leafhopper, Empoasca fabae (Hams), pressure the selections exhibited varying degrees of leafhopper injury. The majority of the EMP lines displayed lower hopperburn scores than 'Ex Rico 23' white navy bean. In 1994 and 1995 the selected EMP lines were planted in small field plots at Ridgetown along with locally adapted bean cultivars of high susceptibility, moderate susceptibility, and moderate resistance. Numbers of nymphs varied among genotypes with some EMP lines sustaining concomitant low nymphal populations and low hopperburn scores, suggesting an antixenosis effect. However, several EMP lines exhibiting low hopperburn scores sustained high numbers of nymphs suggesting a tolerant mode of resistance. Uniformity of adult leafhopper populations among plots suggests that the mechanism of resistance has no effect on adult populations. The data from these experiments demonstrate that there is a high level of resistance to potato leafhoppers in several of the breeding lines obtained from CIAT, such as EMP 423 and EMP 419, and that many of these lines are adapted to the growing conditions of southern Ontario.